Blow-up phenomena for the rotation-two-component Camassa–Holm system. Issue 3 (17th February 2021) - Liu, Jingjing
Abstract : In this paper, we study blow-up phenomena for the rotation-two-component Camassa–Holm (R2CH) system, a model of equatorial water waves that includes the effect of the Coriolis force. We first derive the precise blow-up scenario for R2CH with σ > 0. Then, we present two new blow-up results for strong solutions to the system and then the precise blow-up rate for strong solutions to the system is given.